Optimal Planning of Radial Distribution Networks - Omer, Ankur (My University, 2013)
Large scale distribution system planning is a complex and reasonably difficult problem. This thesis proposes the application of simple and efficient mathematical algorithms for the optimal design of large scale distribution systems in order to provide optimal locating of the high and medium voltage (HV and MV) substations, as well as medium voltage (MV) feeders routing, using their corresponding fixed and variable costs associated with operational and technical constraints. The novel approach presented in the report solves hard optimization problems with different technical constraints in large scale distribution networks. This report presents a new concept based on Dijkstra’s Algorithm introduced for optimal routing of MV substations, followed by new methodology based on graph theory and differential evolution for optimal locating of the substations in a real size distribution network. In the present article to reduce computational burden and avoid huge search space leading to infeasible solutions, special coding methods are generated to solve optimal feeders routing. The proposed coding methods guarantee the validity of the solution toward the global optimal solution. The developed algorithms software is tested in distribution system and the results are presented.
ME, EIED
Keywords: Planning, Radial; Feeder, VSI